AB0787 The eular systemic sclerosis impact of disease (SCLEROID) score – a new patient-reported outcome measure for patients with systemic sclerosis. (12th June 2018) - Dobrota, R.; Becker, M.O.; Fligelstone, K.; Fransen, J.; Tyrrell Kennedy, A.; Allanore, Y.; Carreira, P.; Czirjak, L.; Denton, C.; Hesselstrand, R.; Sandqvist, G.; Kowal-Bielecka, O.; et al.
Abstract : Background: Patient reported outcome measures (PROs) are increasingly important for clinical practice and research. Given the unmet need for a comprehensive PRO for systemic sclerosis (SSc), the ScleroID questionnaire was developed by a joint team of patients with SSc and medical experts in the field. This approach was designed as a brief, specific, patient-derived, disease impact score for research and clinical use in SSc. A preliminary analysis was previously reported. Here, we present the first computation of the ScleroID score and an extended pre-final analysis from the ongoing ScleroID validation study. Methods: This EULAR-endorsed project involves 11 European expert SSc centres. Patients fulfilling the ACR/EULAR 2013 criteria were prospectively included since 05/16 in the ongoing observational cohort study. Patients completed the ScleroID questionnaire (figure 1), as well as the selected comparators mSHAQ, EQ5D, and SF36. Additionally, they weighted the 10 dimensions of the ScleroID by distributing 100 points according to the perceived impact on their health. The final score calculation was based on the ranking of the weights. The study included a reliability arm (follow-up questionnaire 7–10 days from baseline), as well as a longitudinal arm, looking at sensitivity to change at follow-up visits after 6 and 12 months from baseline. Results: As of January 2018, the study cohort included 417 patients with valid baseline data, 80 patients also had a reliability visit and 42 patients a follow-up visit. 84% of patients were female, 62% had limited cutaneous SSc, mean age was 56 years, and median disease duration 10 years. 19% of patients were not able to work. The highest weights by the patients were assigned to Raynaud`s phenomenon, fatigue, hand function and pain, in accordance with our previous results. The total ScleroID score showed good Spearman correlation coefficients with the comparators (mSHAQ, 0.59; EQ5D −0.62; Patient's global assessment, VAS 0.75; SF36 physical score −0.62; each p<0.001). The internal consistency was good with a high Crohnbach's alpha by 0.86. Conclusions: The EULAR ScleroID score is a promising, novel PRO tool designed for use in clinical practice and clinical trials to display the disease impact of SSc, showing good performance in this pre-final analysis. Importantly, Raynaud`s phenomenon, impaired hand function, pain and fatigue were the main patient reported drivers of disease impact. To date the recruitment has reached more than 80% of the targeted number, the study is ongoing. Disclosure of Interest: R. Dobrota: None declared, M. Becker: None declared, K. Fligelstone: None declared, J. Fransen: None declared, A. Tyrrell Kennedy: None declared, Y. Allanore Grant/research support from: Bristol-Myers Squibb, Roche/Genentech, Inventiva, Pfizer, Sanofi, and Servier, Consultant for: Actelion, Bayer, Roche/Genentech, Inventiva, Medac, Pfizer, Sanofi, Servier, and UCB, P. Carreira: None declared, L. Czirjak: None declared, C. Denton Consultant for: Roche/Genentech, Actelion, GlaxoSmithKline, Sanofi-Aventis, Inventiva, Boehringer-Ingelheim, CSL Behring, EMD Serono, Inventiva, and UCB Pharma, R. Hesselstrand: None declared, G. Sandqvist: None declared, O. Kowal-Bielecka: None declared, C. Bruni: None declared, M. Matucci-Cerinic: None declared, C. Mihai: None declared, A. Gheorghiu: None declared, U. Müller-Ladner: None declared, M. Vonk: None declared, I. Olsen: None declared, T. Heiberg: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Mitsubishi Tanabe Pharma and Roche, Consultant for: Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa and UCB